Head-To-Head Comparison of Biological Behavior of Biocompatible Polymers Poly(Ethylene Oxide), Poly(2-Ethyl-2-Oxazoline) and Poly[N-(2-Hydroxypropyl)Methacrylamide] as Coating Materials for Hydroxyapatite Nanoparticles in Animal Solid Tumor Model - Novy, Zbynek; Lobaz, Volodymyr; Vlk, Martin; Kozempel, Jan; Stepanek, Petr; Popper, Miroslav; Vrbkova, Jana; Hajduch, Marian; Hruby, Martin; Petrik, Milos (Nanomaterials (Basel, Switzerland), 2020)
Nanoparticles (NPs) represent an emerging platform for diagnosis and treatment of various diseases such as cancer, where they can take advantage of enhanced permeability and retention (EPR) effect for solid tumor accumulation. To improve their colloidal stability, prolong their blood circulation time and avoid premature entrapment into reticuloendothelial system, coating with hydrophilic biocompatible polymers is often essential. Most studies, however, employ just one type of coating polymer. The main purpose of this study is to head-to-head compare biological behavior of three leading polymers commonly used as "stealth" coating materials for biocompatibilization of NPs poly(ethylene oxide), poly(2-ethyl-2-oxazoline) and poly[N-(2-hydroxypropyl)methacrylamide] in an in vivo animal solid tumor model. We used radiolabeled biodegradable hydroxyapatite NPs as a model nanoparticle core within this study and we anchored the polymers to the NPs core by hydroxybisphosphonate end groups. The general suitability of polymers for coating of NPs intended for solid tumor accumulation is that poly(2-ethyl-2-oxazoline) and poly(ethylene oxide) gave comparably similar very good results, while poly[N-(2-hydroxypropyl)methacrylamide] was significantly worse. We did not observe a strong effect of molecular weight of the coating polymers on tumor and organ accumulation, blood circulation time, biodistribution and biodegradation of the NPs.
Keywords: poly[N-(2-hydroxypropyl)methacrylamide]; solid tumor; nanoparticles; poly(ethylene oxide); hydroxyapatite; poly(2-ethyl-2-oxazoline); animal model